Ramadan Mubarak - Khan,Saniyasnain (Goodword book, 2024)
This engaging board book introduces young children to the blessings of Ramadan and the joy of Eid ul-Fitr. In simple and relatable words, it explains how fasting teaches patience, self-control, and empathy, while prayer and reading the Quran help bring us closer to Allah. Children learn about compassion, kindness, and good deeds during Ramadan, and the story concludes with the happiness of celebrating Eid with family, food, and togetherness
This book introduces children to the spiritual meaning of Ramadan and the joy of Eid ul-Fitr. It highlights the values of fasting, prayer, and reading the Quran, teaching children about patience, self-discipline, and developing good habits. The story also emphasizes compassion and empathy by encouraging awareness of others$1 (Bneeds. With simple language and colorful illustrations, the book makes the practices and celebrations of Ramadan relatable for young readers. It concludes with the happiness of Eid, symbolizing togetherness, gratitude, and joy with family and friends.s
Age Group: Toddlers and preschoolers (under 5 years) Readers: Young Muslim children, parents, and educators Use: Home reading, classroom/library use, gifts during Ramadan & Eid